Assessment of Vitamin A versus Vitamin E effect on Motility and DNA Integrity of Human Cryopreserved Sperms - Samir Al-Anbari; Mustafa Ibraheem; Thaer Farhan (The Iraqi Journal of Medical Sciences)
Background: It is well known that cryopreservation procedure may result in negative impact on spermatozoa function throughout relative overproduction of reactive oxygen species (ROS). However, ROS overproduction can be corrected by antioxidants. Objective: To find out the effect of vitamin A on cryopreserved spermatozoa throughout measuring their motility rate and DNA fragmentation and compare it with vitamin E effect. Methods: Forty seminal fluid specimens were individually collected from forty healthy, non-drug and non-alcohol consumers, normozoospermic males in Um Al-Baneen Center for Infertility Management and In Vitro Fertilization in Baghdad. To facilitate comparing between used vitamins and experimenting each one alone, those specimens were distributed into 4 groups of 10 specimens each. Following deriving their own controls without any vitamin treatment, specimens of these groups, in general, were treated with two concentrations of vitamin A (20 µg/dl and 30 µg/dl), and two concentrations of vitamin E (10 µmol/l and 20 µmol/l). Then, each specimen was incubated for 1 hour before being cryopreserved in liquid nitrogen for 14 days. Motility percentage and DNA fragmentation were assessed following cryopreservation and thawing of spermatozoa. Results: Results revealed that there were significant statistically differences in post-thawing motility and DNA fragmentation means between specimens treated with vitamin A and their relevant control; between specimens treated with vitamin E and their relevant control; and between specimens treated with vitamin E and those treated with vitamin A among all groups of the study. Conclusion: These results lead to the conclusion that both of vitamin A and E play an important role in improving and protecting sperm motility and DNA integrity following cryopreservation, and vitamin E is more effective than vitamin A. Keywords: Seminal fluid analysis, vitamin A, vitamin E, reactive oxygen species, sperm cryopreservation, sperm DNA fragmentation, sperm motility assessment Citation: Al-Anbari SA, Ibraheem MM, Farhan TM. Assessment of Vitamin A versus Vitamin E effect on Motility and DNA Integrity of Human Cryopreserved Sperms. Iraqi JMS. 2023; 21(1): 43-62. doi: 10.22578/IJMS.21.1.5